Paragraph and Its Development Pattern On The Essay Writing Of Elementary School Students - Herman Budiyono (International Journal of Language Teaching and Education, 2020)
This study aimed to describe the quality of the paragraph and its development pattern in the essay writing of elementary school (Sekolah Dasar – SD) students in Jambi City (Kota Jambi – KJ) (SD-KJ). This study utilized a "quantitative descriptive" design. The population was all essays written by the fifth-grade students of SD-KJ. The sample of this research was 35 paragraphs from the essay writing of the fifth-grade students of SD-KJ. The data analysis steps were searching for frequency distribution of paragraph quality and development pattern; grouping the paragraph frequency distribution according to their quality; counting the percentage of each paragraph quality and type of development pattern; and presenting the results. Regarding to paragraph quality, the results are: (1) paragraph completeness, good (5.71%), poor (68.57%), and bad (25.70%); (2) paragraph unity, good (34.58%); poor (51.42%); and bad (14.28%); (3) paragraph order, good (28.57%); poor (51.42%); and bad (20%); and (4) paragraph coherence, good (54.28%); poor (34.28%); and bad (11.42%). Reffering to the implementation of the paragraph development pattern, the results are paragraph development pattern of comparison and contradiction: 20%, analogy: 5.71%, giving examples: 8.57%, cause and effect: 48.57%; general-specific or specific-general: 11.42%, and classification: 5.71%.